PEMANFAATAN TEPUNG PORANG (Amorphophallusoncophyllus) SEBAGAI PENSTABIL EMULSI M/A DAN BAHAN PENYALUT PADA MIKROKAPSUL MINYAK IKAN - Sri Haryani Anwar, Berlianta Maria Br. Ginting, Yuliani Aisyah, Novi Safriani (Jurnal Teknologi Industri Pertanian, 2017)
This research was aimed to investigate the ability of porang (Amorphophallus oncophyllus) flour to stabilizeoil-in-water (O/W) emulsion and further more can be used as encapsulating matrix for fish oil microencapsules. The experiments were divided into three stages: A) emulsification with ultra turrax to form coarse emulsion which designed using randomized block design with two variables, namely concentration of porang flour (55% glucomanan) i.e. 0.5% and 1% , and oil concentrations i.e.20%, 30% and 40%;B) Variables that produced stable coarse emulsions were selected to be used in fine emulsion process using high pressure homogenizer; and 3) Stable and effective fine emulsions were spray dried to produce fish oil microcapsules. Porang flour used was yellow in colour with 7.75% moisture content, 8% ash, 9.72% crude fiber, 0.43% fat and 55% glucomanan. The statistical analysis showed that all variables i.e. porang flour and oil concentrations influenced the emulsifying activity values and viscosity significantly (P≤0.01). The most stable coarse emulsion was the one that emulsified by 40% oil and 1% porang flour with viscosity of 3647 cP and 100% emulsifying activity, and separation of 2.70 ml serum layer after 7 days storage. Stable fine emulsion was produced by the same variables’ combination as coarse emulsion with average droplet size of 614 nm, polydispersity index of 0.237, emulsion zeta potential of -25.83 mV, and separation of only 0.25 mL after 16 days storage. Emulsion that spray dried effectively contained 0.5% porang flour. The peroxide values of fish oil microcapsules were in the range of 16.5 – 32.5 meq/kg oil. Keywords: porang flour, glucomannan, o/w emulsion, emulsion stability, stabilizer